Internet of Things (IoT) Cybersecurity: Literature Review and IoT Cyber Risk Management - Lee, In (Future internet, 2020)
Along with the growing threat of cyberattacks, cybersecurity has become one of the most important areas of the Internet of Things (IoT). The purpose of IoT cybersecurity is to reduce cybersecurity risk for organizations and users through the protection of IoT assets and privacy. New cybersecurity technologies and tools provide potential for better IoT security management. However, there is a lack of effective IoT cyber risk management frameworks for managers. This paper reviews IoT cybersecurity technologies and cyber risk management frameworks. Then, this paper presents a four-layer IoT cyber risk management framework. This paper also applies a linear programming method for the allocation of financial resources to multiple IoT cybersecurity projects. An illustration is provided as a proof of concept.